Influence of milk quality and cheese-making procedure on functional fatty acid transfer in three Italian dairy products: Mozzarella, Raveggiolo and Ricotta. (15th June 2022) - Buccioni, Arianna; Mannelli, Federica; Daghio, Matteo; Rapaccini, Stefano; Scicutella, Federica; Minieri, Sara
Abstract: Cheese quality traits are affected firstly by milk quality and secondly by processing protocols. The cheese-making procedure plays an important role in the transfer of functional fat components from milk to cheese with important implications on the nutritive value of dairy products. To evaluate the influence of the cheese-making procedure, three fresh Italian cheeses from the same milk bulk, Mozzarella, Raveggiolo and Ricotta were processed and analyzed in terms of fatty acid transfer from milk to dairy products. The fatty acids were transferred with several differences. In particular, C14:0 (P = 0.0011) and C14:1 (P = 0.0007) showed the highest value in Raveggiolo while C16:0 was higher in Raveggiolo and Ricotta (P = 0.0002). Trans -monoene fatty acids have a detrimental effect on human health, however trans C18:1 isomers, from 6 to 10, and trans12 showed no significant differences in transfer from milk to dairy products. In contrast, vaccenic and linoleic acids, which are beneficial fatty acids for human health, were recovered in higher percentages in Raveggiolo than in Mozzarella and Ricotta (P = 0.0188 and P < 0.0001, respectively). The recovery of oleic acid, an antiatherogenic fatty acid, was higher in Ricotta (P < 0.0001). No effect on conjugated linoleic acid was found. Highlights: Dairy products contain fatty acids recognised beneficial for human health. The cheese-making procedure affects the quality of cheeses, especially of fresh ones. The transfer of functional fatty acids from milk to cheeses is affected by cheese-making procedure.